2022
DOI: 10.1029/2021jc017645
|View full text |Cite
|
Sign up to set email alerts
|

Variability and Dynamics of Along‐Shore Exchange on the West Antarctic Peninsula (WAP) Continental Shelf

Abstract: The continental shelf of the West Antarctic Peninsula (WAP) is characterized by strong along‐shore hydrographic gradients resulting from the distinct influences of the warm Bellingshausen Sea to the south and the cold Weddell Sea water flooding Bransfield Strait to the north. These gradients modulate the spatial structure of glacier retreat and are correlated with other physical and biochemical variability along the shelf, but their structure and dynamics remain poorly understood. Here, the magnitude, spatial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(40 citation statements)
references
References 80 publications
(154 reference statements)
3
35
0
Order By: Relevance
“…However, because the MLD plays a role in determining residence time, differences between ROMS modeled MLD and actual MLD could play an important role in interpreting these results. If summer MLDs are shallower than the model predicts (Hudson et al, 2021;Wang et al, 2022), real migrating zooplankton over PDC may spend less time in the low residence time surface layer compared to our simulations. Therefore, the observed migrations to 50 m may still result in increased residence times, however, MLD predictions by ROMS need to be improved to test this hypothesis.…”
Section: Direct Observations Of Dvmmentioning
confidence: 54%
See 1 more Smart Citation
“…However, because the MLD plays a role in determining residence time, differences between ROMS modeled MLD and actual MLD could play an important role in interpreting these results. If summer MLDs are shallower than the model predicts (Hudson et al, 2021;Wang et al, 2022), real migrating zooplankton over PDC may spend less time in the low residence time surface layer compared to our simulations. Therefore, the observed migrations to 50 m may still result in increased residence times, however, MLD predictions by ROMS need to be improved to test this hypothesis.…”
Section: Direct Observations Of Dvmmentioning
confidence: 54%
“…Residence times were greatest in the presence of shallower MLD, supporting our hypothesis that a thinner surface layer, indicated by a shallower MLD, increases migrating zooplankton residence times. Importantly, ROMS predicts deeper MLD and less stratification during the summer in PDC (Hudson et al., 2021; Wang et al., 2022). A shallower, more stratified surface ocean means that it is more isolated from deeper water masses.…”
Section: Discussionmentioning
confidence: 99%
“…Comparisons of in situ observations from the 2019−2020 austral summer and ROMS simulations from the same austral summer simulated here illustrate that the subsurface eddy over PDC is more baroclinic than simulations predict (Hudson et al 2021). The model also predicts deeper mixed layers than observed by autonomous underwater gliders deployed within the region, suggesting that stratification is under-predicted in the model over PDC (Hudson et al 2021, Wang et al 2022. This has led to the hypothesis that surface waters are more isolated from the effects of the canyon than the model suggests and would explain why the eddy is often visible in the surface in the model (Hudson et al 2021, this study) but is only observed in surface currents when stratification and winds are low (Hudson et al 2021).…”
Section: Assumptions About Dvm Krill and Penguin Behaviormentioning
confidence: 70%
“…Sea surface temperature has been found to be an important covariate influencing the habitat selection of humpback whales in the Southern Ocean (e.g., Andrews-Goff et al, 2018;Bestley et al, 2019;Riekkola et al, 2019;Reisinger et al, 2021). Johannessen et al (2022) observed a positive correlation between humpback whale presence and sea surface temperature in the Bransfield Strait region, and interpret this as a preference for the warm, nutrient-rich Circumpolar Deep Water that is delivered onto the continental shelf (Martinson & McKee, 2012;Wang et al, 2022), driving marine productivity (e.g., Ducklow et al, 2012).…”
Section: Discussionmentioning
confidence: 99%